Silkworms - Schaffer, Donna (Mankato, Minn. : Bridgestone Books, 1999)
Describes the physical characteristics, habits and stages of development of silkworms, as well as how they are raised to produce silk.
Includes bibliographical references (p. 23) and index.
Booklist.
3.9
K-3
Keywords: Silkworms -- Life cycles -- Juvenile literature; Silkworms; Silkworms; Silkworms; Worms; Silk